The comparison of colchicine and standard treatment in COVID-19 patients: A mini review - Yasmeen Kwok; Dwi Aris Agung Nugrahaningsih; Woro Rukmi Pratiwi (Indonesian Journal of Pharmacology and Therapy, 2021)
Coronavirus disease 2019 (COVID-19) was declared a pandemic in March 2020. There are several drugs used at different stages of the disease, but none seem to be completely effective. In the absence of any known therapy, many drugs have been tested, including colchicine. Colchicine differs from these other therapies in having pleiotropic mechanism of action, being less potent on any single target, and being an oral agent. It is also a better option since colchicine is not immunosuppressive, is not known to increase risk of infection, and is inexpensive. The aim of this study was to provide evidence of the role of colchicine in improving clinical outcome and reducing death rate of COVID-19 patients through literature mini-review. A mini-review, composed of previous RCTs comparing the use of colchicine in COVID-19 with standard care or placebo under the keyword “COVID-19”, “COVID”, “coronavirus”, “SARS-CoV-2”, “coronavirus disease”, “Colchicine”, “CAS 64-86-8”, “standard treatment”, “standard care”, “standard of care”, “common treatment”, “placebo”, “clinical improvement”, and “clinical response”.  The addition of colchicine to standard treatment can be beneficial in treating COVID-19. Studies included showed that colchicine has significantly improved time to clinical deterioration compared to the control group. Colchicine reduced the length of hospitalization and the need for supplemental oxygen therapy. One of the included studies mentioned that in outpatient settings, colchicine can prevent hospitalization and even death. Colchicine can improve the clinical outcome on CRP levels, the number of patients that need mechanical ventilation, and death rate in COVID-19 patients. The addition of colchicine to standard treatment should be considered to prevent clinical deterioration and death. Colchicine reduces the number of adverse effects in COVID-19 patients except for gastrointestinal adverse effects, especially diarrhea, which is consistently more common in the colchicine groups.